PENGARUH SISTEM PENGENDALIAN INTERNAL PIUTANG TERHADAP PIUTANG MACET PADA KOPERASI SIMPAN PINJAM KOPDIT SWASTI SARI DI KANTOR PUSAT KUPANG - Aplonia Atto (Politeknik Negeri Ambon, 2026)
Introduction: This study investigates the effect of internal control systems on bad debts at the Swasti Sari Credit Union Head Office in Kupang for the period 2021–2023. The rising trend of non-performing loans (NPLs) poses a significant challenge for cooperatives, underscoring the need for an effective internal control system.Methods: The research adopts a quantitative approach using simple linear regression analysis. Data were collected through questionnaires distributed to employees and management involved in loan processing and monitoring. The validity and reliability of the data were tested using SPSS version 21.Results: The internal control system does not have a significant effect on bad debts. The regression equation obtained is Y = 39.314 + 0.145X, with a significance value (p-value) of 0.709 (> 0.05) and a t-count of 0.376, which is lower than the t-table value (2.037). However, the coefficient of determination (R²) is 0.764, indicating that internal control systems can explain 76.4% of the variation in bad debts. In comparison, the remaining 23.6% is influenced by other factors not examined in this study.Conclusion: Although the internal control system contributes to reducing bad debts, its effect is not statistically significant. Other factors, such as credit policy, organizational structure, and collection procedures, should also be considered in strengthening credit management. Keywords: Bad Debt, Credit Union, Financial Control, Internal Control System, Loan Management